MINIMAX PROBLEM FOR THE ROMANOVSKY DISTRIBUTION IN THE Lγ METRIC (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article solves the minimax problem for the Romanovsky distribution in the Lj metric.Convergence theorems for variation of the Romanovsky distribution to normal, binomial,negative-binomial distributions, Poisson distributions, Erlang distributions, and betdistributions are given.